Cost Analysis and Preparation of Cost of Production at UD. Umega Bean Bread Hj. Eliya Lubis”High Club City - Vina Winda Sari (Trigin Publisher, 2022)
Currently, the Tebing Tinggi area sells a wide variety of foods, one of which is the peanut bread. Peanut bread is one of the typical Tebing Tinggi souvenirs. The ever increasing demand has made peanut bread business owners compete in attracting consumers. Such as Rajawali Peanut Bread, Raja Beo Peanut Bread, Raja Peanut Bread and Hj Elya Lubis Peanut Bread. Hj Eliya Lubis peanut bakery, this bakery business is a household industry for Mrs. Hj's family. Eliya Lubis with her husband Hayul Amin Nasution, this business has been running for six years. Currently Hj Elya Lubis's peanut bread has various flavors of the peanut bread products it produces